Social and ecological factors alter stress physiology of Virunga mountain gorillas (Gorilla beringei beringei). Issue 9 (1st April 2019) - Eckardt, Winnie; Stoinski, Tara S.; Rosenbaum, Stacy; Santymire, Rachel
Abstract: Living in a rapidly changing environment can alter stress physiology at the population level, with negative impacts on health, reproductive rates, and mortality that may ultimately result in species decline. Small, isolated animal populations where genetic diversity is low are at particular risks, such as endangered Virunga mountain gorillas ( Gorilla beringei beringei ). Along with climate change‐associated environmental shifts that are affecting the entire population, subpopulations of the Virunga gorillas have recently experienced extreme changes in their social environment. As the growing population moves closer to the forest's carrying capacity, the gorillas are coping with rising population density, increased frequencies of interactions between social units, and changing habitat use (e.g., more overlapping home ranges and routine ranging at higher elevations). Using noninvasive monitoring of fecal glucocorticoid metabolites (FGM) on 115 habituated Virunga gorillas, we investigated how social and ecological variation are related to baseline FGM levels, to better understand the adaptive capacity of mountain gorillas and monitor potential physiological indicators of population decline risks. Generalized linear mixed models revealed elevated mean monthly baseline FGM levels in months with higher rainfall and higher mean maximum and minimum temperature, suggesting that Virunga gorillas might be sensitive to predicted warming and rainfall trends involving longer, warmer dry seasons and more concentrated and extreme rainfall occurrences. Exclusive use of smaller home range areas was linked to elevated baseline FGM levels, which may reflect reduced feeding efficiency and increased travel efforts to actively avoid neighboring groups. The potential for additive effects of stress‐inducing factors could have short‐ and long‐term impacts on the reproduction, health, and ultimately survival of the Virunga gorilla population. The ongoing effects of environmental changes and population dynamics must be closely monitored and used to develop effective long‐term conservation strategies that can help address these risk factors. Abstract : We investigated how social and ecological variation affect basal fecal glucocorticoid metabolite concentrations in wild Virunga mountain gorillas, to better understand their adaptive capacity and monitor potential physiological indicators of population decline risks. Rainfall, temperature, and exclusive home range size of a group negatively affected stress physiology of this critically endangered population. Findings indicate that effects of climate change and increasing population density must be closely monitored and used to develop effective long‐term conservation strategies that can help address these risk factors.